Characterization of monoclonal antibodies to heat-labile enterotoxin encoded by a plasmid from a clinical isolate of Escherichia coli. - Belisle, B W (1984)
Eight selected hybridoma cell lines that produced monoclonal antibodies against heat-labile enterotoxin from an Escherichia coli strain of human origin (LTh) were characterized. Antibodies produced by these cell lines were tested for binding specificity in a series of solid-phase radioimmunoassays and Western blots by using as test antigens LTh, the A, A1, A2, and B polypeptides of LTh, the heat-labile enterotoxin from an E. coli strain of porcine origin, and cholera toxin. The monoclonal antibodies were also tested for isotype and ability to neutralize LTh. Two of the anti-LTh monoclonal antibodies cross-reacted with cholera toxin, and six were specific for determinants of LTh that were not present on cholera toxin. One was specific for a unique epitope of LTh that was not shared by the heat-labile enterotoxin from an E. coli strain of porcine origin or cholera toxin. Four antibodies specific for epitopes on the B subunit of LTh (LTh-B) reacted with pentameric LTh-B but did not react in Western blots with monomeric LTh-B. The remaining four antibodies were specific for epitopes on LTh-A; two of these antibodies bound to A1, one reacted with A2, and one recognized only intact LTh-A. Only one monoclonal antibody had detectable neutralizing activity, and it was specific for LTh-A.